Bridging the Gap: Securitizing Lack of Accessible Education in Indonesia During the Covid-19 Pandemic - Aloysius Efraim Leonard; Ruth Latreia Theo Saphira (Institute of International Studies, 2020)
The Global South continues to face new threats and challenges posed by the COVID-19 pandemic. The debate over health and economy continues and often leaves one aspect out of the equation: education. Especially in Southeast Asia, where regional and domestic disparity still lingers. Association of Southeast Asia Nations (ASEAN) acknowledged that the development gap remained one of the most crucial issues in the region. Using Wæver and Buzan’s securitization theory and Japanese approach of human security, the article tries to prove why the current state of education should be considered as a new non-traditional security threat and should be securitized by countries in the region. The article will use a qualitative method and hypothesizes that the inability for states to ensure quality education during the pandemic will affect the quality of the states’ human capital. The pandemic forces education institutions to rely on online learning. However, not every student has access towards required facilities such as, internet connection, gadgets, technologies, etc. Students in underdeveloped areas might struggle to participate in online classes, forcing them to be left behind. In the long-run, this will slow down Southeast Asian countries’ progress in tackling the development gap.